Survival and Prognosis Analysis of Bortezomib Based Regimen in Newly Diagnosed Super-aged Multiple Myeloma Patients - ZHAO Fengyi, LI Xin, ZHAN Xiaokai, ZHANG Jiajia, SHEN Man, TANG Ran, FAN Sibin, HUANG Zhongxia (Zhongguo quanke yixue, 2024)
Background Multiple myeloma is a highly heterogeneous disease. Super-aged patients with multiple myeloma are a special group. There is a lack of evidence-based medical basis in the treatment decision and general evaluation of them, and there is also some controversy in the assessment of frailty. Objective To explore the clinical features and the influencing factors of survival and prognosis in newly diagnosed super-aged multiple myeloma (MM) patients with the bortezomib based regimen and to evaluate the best assessment model for the general status of patients with MM. Methods The clinical data of newly diagnosed super-aged patients with MM in Beijing Chao-yang Hospital, Capital Medical University from November 2013 to January 2023 were retrospectively analyzed. Survival follow-up was conducted through the medical record system of Beijing Chao-Yang Hospital, Capital Medical University until April 1, 2023, with the end points of this study of overall survival (OS) and progression-free survival (PFS) . The patients were divided into the two-drug treatment group (n=18) and three-drug treatment group (n=11) , and the clinical and genetic characteristics of the two groups were compared. The Geriatric Assessment System (GA) score, UK Myeloma Research Alliance Risk Profie (MRP) score, and Mayo score were used to evaluate the frailty status and treatment efficacy. Survival curves of OS and PFS in MM patients were plotted using the Kaplan-Meier method. Log-rank test was used to compare the survival curves of different influencing factors. Multivariate Cox hazard risk regression analysis was used to explore the influencing factors of OS and PFS in MM patients. Results The median PFS was 8.70 (1.90-43.87) months and the median OS was 17.23 (2.00-72.83) months. A total of 21 (72.41%) patients experienced disease progression (PD) or relapse, and 12 (41.38%) patients died by the final follow-up. The objective remission rate (ORR) for first-line treatment was 82.76% (24/29) , the partial remission (PR) rate was 51.72% (15/29) , the very good partial remission (VGPR) rate was 24.14% (7/29) , and the complete remission (CR) rate was 6.90% (2/29) . There was no significant difference in CR rate, VGPR rate, PR rate and ORR between the two groups of newly diagnosed super-aged MM patients (P>0.05) . Multivariate Cox hazard risk regression analysis showed that MRP debilitation (HR=0.213, 95%CI=0.049-0.924, P=0.039) , elevated serum corrected calcium (HR=0.153, 95%CI=0.041-0.570, P=0.005) and maintenance therapy (HR=4.301, 95%CI=1.219-15.169, P=0.023) were independent influencing factors of PFS in newly diagnosed super-aged MM patients, while maintenance treatment (HR=4.372, 95%CI=1.049-18.221, P=0.043) was an independent influencing factor for OS in newly diagnosed super-aged MM patients. Conclusion There is no significant difference in the efficacy and prognostic impact of two-drug or three-drug Bortezomib based treatment. Serum corrected calcium elevation and maintenance therapy are independent prognostic factors for survival. MRP score can be used to assess the prognosis of newly diagnosed super-aged MM patients.